Association of type 2 diabetes, hypertension, and hyperlipidemia with immune-related adverse events in patients undergoing immune checkpoint inhibitors therapy - Li, Ruidan; Mu, Xiaoli; Liu, Zheran; Huang, Rendong; Peng, Xingchen (Frontiers in Immunology, 2025)
AimsImmune-related adverse events (irAEs) pose a significant challenge to the clinical use of immune checkpoint inhibitors (ICIs) in cancer immunotherapy. This study aims to determine whether comorbid conditions such as type 2 diabetes (T2DM), hypertension, and hyperlipidemia affect the risk of irAEs in cancer patients receiving ICIs treatments.Materials and methodsWe conducted a retrospective analysis of clinical data from 3,489 cancer patients treated with ICIs (anti-PD-1, anti-PD-L1, and anti-CTLA-4) at West China Hospital of Sichuan University from 2017 to 2022. Logistic regression models were used to evaluate the associations between T2DM, hypertension, and hyperlipidemia with irAEs. Subgroup analyses assessed irAEs in patients with and without these comorbidities across different cancer types. Additionally, we explored the associations between comorbidities and irAEs affecting different organs.ResultsThe results showed that comorbid T2DM, hypertension, and hyperlipidemia significantly increased the risk of irAEs in all cancer types (T2DM: OR=1.40, 95% CI: 1.12-1.74, p=0.003; hypertension: OR=1.21, 95% CI: 1.00-1.45, p=0.049; hyperlipidemia: OR=1.62, 95% CI: 1.02-2.53, p=0.038). T2DM primarily increased the risk of irAEs in lung cancer patients (OR = 1.50, 95% CI: 1.12-2.01, FDR-adjusted p = 0.036), and all three comorbidities significantly elevated the risk of cardiac irAEs.ConclusionsOur study is the first to confirm an association between T2DM, hypertension, and hyperlipidemia and the occurrence of irAEs in cancer patients receiving ICIs therapy. This finding highlights the critical need for clinicians to perform comprehensive evaluations of patients’ comorbidities prior to treatment.